2018
DOI: 10.1159/000488684
|View full text |Cite
|
Sign up to set email alerts
|

Battery Longevity Comparison of Two Commonly Available Dual Channel Implantable Pulse Generators Used for Subthalamic Nucleus Stimulation in Parkinson’s Disease

Abstract: Objectives: Deep brain stimulation for Parkinson’s disease (PD) utilises an implantable pulse generator (IPG) whose finite lifespan in non-rechargeable systems necessitates their periodic replacement. We wish to determine if there is any significant difference in longevity of 2 commonly used IPG systems; the Medtronic Kinetra, and the Medtronic Activa Primary Cell (PC), which has come to replace it. Methods: All patients with bilateral Subthalamic Nucleus stimulators for PD performed in our centre were include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 23 publications
(32 reference statements)
2
11
0
Order By: Relevance
“…Decreased longevity of the Activa ® PC, as compared to the Kinetra ® , has been proposed in STN DBS for PD but no such differences could be seen in this study, which is in line with previous sparse data regarding older IPG models in DBS for dystonia [12,13,[31][32][33]. Possibly, the lower energy consumption and prolonged IPG longevity in STN DBS more clearly separate the differences in longevity between Kinetra ® and Activa ® PC.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Decreased longevity of the Activa ® PC, as compared to the Kinetra ® , has been proposed in STN DBS for PD but no such differences could be seen in this study, which is in line with previous sparse data regarding older IPG models in DBS for dystonia [12,13,[31][32][33]. Possibly, the lower energy consumption and prolonged IPG longevity in STN DBS more clearly separate the differences in longevity between Kinetra ® and Activa ® PC.…”
Section: Discussionsupporting
confidence: 89%
“…Previous investigations of IPG longevities are devoid of information regarding DBS electrode locations in relation to the target [12,13,32,33]. Suboptimal electrode placement could constitute a confounding factor when comparing energy consumption and IPG longevity between cohorts as increased stimulation energy might be necessary in order to obtain a sufficient therapeutic effect [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…The authors show that the newer generation of Medtronic's DBS IPGs (the dualchannel Activa PC and the single-channel Activa SC) has a much shorter battery life than the older dual-channel Kinetra and single-channel Soletra. This confirms the impression of many workers with large experience in DBS and also corroborates previous published reports from Seoul, Kiel, Berlin, Birmingham, Tel Aviv and Grenoble [2,6,7,10,11,16] establishing that the older brands of IPGs "Kinetra" and "Soletra" had a battery lasting up to twice as long as the newer brands Activa PC and Activa SC. The analysis of the data in the present paper from Clermont-Ferrand is very solid, and the authors show that the older batteries lasted twice as long as the newer ones.…”
supporting
confidence: 90%
“…The Activa series is currently the most commonly implanted IPG. The Activa PC is smaller in size (volume of 37 cm 3 ) and was proposed to have a longer battery life; however, studies have found a significant shorter life span for the Activa PC than for the Kinetra [ 60 , 61 ]. Subsequent additions to the Activa series included the rechargeable dual-channel Activa RC (22 cm 3 , approved in South Korea in 2010) and the single-channel nonrechargeable Activa SC (27 cm 3 ).…”
Section: Update On Devicesmentioning
confidence: 99%